Archaeological, Paleontological and Genomic Perspectives on Late European Neandertals at Vindija Cave, Croatia - Janković, Ivor; Ahern, James C. M.; Mauch Lenardić, Jadranka; Brajković, Dejana; Smith, Fred H.; Karavanić, Ivor (2011)
The Late Pleistocene sediments of Vindija Cave, NW Croatia, yield paleontological and archaeological finds that have an important role in understanding the patterns of late Neandertal/early modern human interaction and succession. The youngest securely dated Neandertal remains in Europe, found in association with an archaeological assemblage exhibiting a mixture of Middle and Upper Paleolithic elements, come from the G complex of this site. Assessments of both old and new data, as well as the results of newer analyses on the finds from Vindija are discussed in the light of the new revision of chronostratigraphic sequences of several important European sites. Further, the new genomic data obtained from the Vindija sample is included in a discussion on the problems, results and patterns of Late Pleistocene hominin evolution and possible population interaction patterns between Neandertals and early modern humans in Europe.
Projekt MZOS
Projekt MZOS
Projekt MZOS
ENG